Effect of Natural Phytase, Fermentation, and Baking Processes on Phytate Degradation in Wheat Bread Manufactured from Local Mills Flour - Nasser, Jassim M.; Hammood, Ezuldeen K. (Iraqi Journal of Science, 2019)
The present study aims to investigate the effect of wheat natural phytase, fermentation and baking processes in the destruction of phytic acid during the process of making wheat bread for some Iraqi mills. The concentration of phytic acid was (850.32, 802.14, 531.84 mg / 100g) for the flour of AL-Brairie, AL-Nesr and AL-Al-Doura mills respectively. At the end of the fermentation processes, the decrease in the concentration of phytic acid in the samples produced from the flour obtained from the three mills was (47.06, 26.98, 40.00%) respectively, while inorganic phosphorus concentration in all treatments increased by 32.4, 42.37 and 36.21 %, respectively. It was found that the activity of wheat natural phytase enzyme varies according to the type of mill and the enzyme has been destroyed after the baking process for all treatments. It is clear that, with the effect of wheat natural phytase enzyme and fermentation and baking processes, the concentration of phytic acid may be reduced when preparing wheat bread for some mills by (26-47%).